2009
DOI: 10.3989/scimar.2009.73n3449
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the early life ecology of <em>Sardina pilchardus</em> (Walbaum, 1792) in the northern Iberian Atlantic

Abstract: SUmmarY: in the atlantic iberian estuaries, sardines tend to be a minor component of the ichthyoplankton assemblages, with rare occurrence largely restricted to estuarine mouths. However, this was not the case of the lima estuary (nW Portugal), where sardines were the most abundant and frequently occurring marine taxon of the larval fish assemblages. abundance of sardines collected during a two-year survey (2002)(2003)(2004) ranged from 0.5 to 60.8 larvae/100 m 3 , with the majority still showing yolk and unpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
2
13
1
Order By: Relevance
“…On the other hand, sardine S. pilchardus larvae were more abundant at the sea and were only present in small numbers in the lower sections of the estuary. Such spatial distribution is typical of marine stragglers, although S. pilchardus was classified as marine migrant species, in accordance with the classification proposed by Franco et al (2008) and also corroborating previous studies in the Lima estuary during which high abundances of S. pilchardus larvae were observed in the inner sections of the estuary (Ramos et al 2009). European sardine larvae tend to dominate the D r a f t ichthyoplankton community in the Western Iberian upwelling ecosystem, particularly during colder months of the year (Garrido et al 2009) and are thought to be limited to coastal areas (e.g.…”
Section: Larval Fish Dispersal According To Species Functional Traitssupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, sardine S. pilchardus larvae were more abundant at the sea and were only present in small numbers in the lower sections of the estuary. Such spatial distribution is typical of marine stragglers, although S. pilchardus was classified as marine migrant species, in accordance with the classification proposed by Franco et al (2008) and also corroborating previous studies in the Lima estuary during which high abundances of S. pilchardus larvae were observed in the inner sections of the estuary (Ramos et al 2009). European sardine larvae tend to dominate the D r a f t ichthyoplankton community in the Western Iberian upwelling ecosystem, particularly during colder months of the year (Garrido et al 2009) and are thought to be limited to coastal areas (e.g.…”
Section: Larval Fish Dispersal According To Species Functional Traitssupporting
confidence: 90%
“…Spring was chosen as many winter/spring marine spawning species colonize northern Portuguese estuaries during this season (Ramos et al 2006), including important marine resources as sardine (Ramos et al 2009) and flounder (Ramos et al 2010).…”
Section: Fish Larvae Samplingmentioning
confidence: 99%
“…larvae (Santos et al, 2004Ramos et al, 2009b). On the other hand, the increase in intensity and frequency of upwelling events during the winter spawning season of small pelagic species off the coast of Portugal was found to have a negative impact on recruitment, limiting their survival success (Santos et al, 2001).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Yearly peaks in sardine recruitment are generally found in winter (1985Stratoudakis et al, 2003) but general models did not identify seasonal relationships in this season to be detrimental to sardine fisheries. Other studies showed that S. pilchardus recruitment is linked to local winter wind conditions that can have both positive and negative effects on larvae survival (Santos et al, 2011;Porteiro et al, 1996;Ramos et al, 2009) and recruitment of pelagic species (Bakun and Parrish, 1991;Lloret et al, 2004), suggesting that larvae survivorship is closely related to vertical mixing and, consequently, to wind stress as a contributing mechanism to fisheries.…”
Section: General Remarksmentioning
confidence: 99%
“…Variability in the distribution, abundance, and size of populations of pelagic fish may also in some cases be better explained by hydrographic properties, such as currents and geographical features of the coast and bottom (Checkley et al, 2009). The underlying mechanisms for population variability of small pelagic fish have also been described and discussed in regard to future climate variability Borges et al, 2003;Cury et al, 2000;Porteiro et al, 1996;Ramos et al, 2009;Silva et al, 2006;Lloret et al, 2004).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%